Modulation of Mucosal Immune Response, Tolerance, and Proliferation in Mice Colonized by the Mucin-Degrader Akkermansia muciniphila - Derrien, Muriel; van Baarlen, Peter; Hooiveld, Guido; Norin, Elisabeth; Muller, Michael; de Vos, Willem (Frontiers in Microbiology, 2011)
Epithelial cells of the mammalian intestine are covered with a mucus layer that prevents direct contact with intestinal microbes but also constitutes a substrate for mucus-degrading bacteria. To study the effect of mucus degradation on the host-response, germ-free mice were colonized with Akkermansia muciniphila. This anaerobic bacterium belonging to the Verrucomicrobia is specialized in the degradation of mucin, the glycoprotein present in mucus, and found in high numbers in the intestinal tract of human and other mammalian species. Efficient colonization of A. muciniphila was observed with highest numbers in the cecum, where most mucin is produced. In contrast, following colonization by Lactobacillus plantarum, a facultative anaerobe belonging to the Firmicutes that ferments carbohydrates, similar cell-numbers were found at all intestinal sites. Whereas A. muciniphila was located closely associated with the intestinal cells, L. plantarum was exclusively found in the lumen. The global transcriptional host response was determined in intestinal biopsies and revealed a consistent, site-specific and unique modulation of about 750 genes in mice colonized by A. muciniphila and over 1500 genes after colonization by L. plantarum. Pathway reconstructions showed that colonization by A. muciniphila altered mucosal gene expression profiles towards increased expression of genes involved in immune responses and cell fate determination, while colonization by L. plantarum led to up-regulation of lipid metabolism. These indicate that the colonizers induce host responses that are specific per intestinal location. In conclusion, we propose that A. muciniphila modulates pathways involved in establishing homeostasis for basal metabolism and immune tolerance towards commensal microbiota.